1998
DOI: 10.1080/004982598239687
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 2,2 ,4,4-tetrabromodiphenyl ether in rat and mouse

Abstract: 1. The distribution and excretion of orally administered 14C-labelled 2,2',4,4'-tetrabromodiphenyl ether (TBDE) have been studied in rat and mouse. 2. TBDE was efficiently absorbed and stored in adipose tissue where high concentrations were observed in both species. 3. In the rat, 86% of the dose was retained after 5 days, while 14% was excreted via the faeces and < 0.5% via the urine. 4. The mouse excreted 20% of the dose via the faeces and 33% via the urine, the latter as a hydrophilic and labile metabolite.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
58
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 0 publications
11
58
0
Order By: Relevance
“…Partitioning of PBDEs into the (fetal) brain is detected in wildlife (Basu et al 2007; Gebbink et al 2008; Montie et al 2009) and toxicokinetics studies, often by using radiolabeled PBDEs (Örn and Klasson-Wehler 1998; Riu et al 2008; Staskal et al 2006a, 2006b). In contrast, recent experimental and wildlife studies have shown that OH-PBDEs are usually not detectable in brain, although OH-PBDEs were detected in brain and cerebrospinal fluids of marine mammals (Gebbink et al 2008; Montie et al 2009; Zhang et al 2008).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Partitioning of PBDEs into the (fetal) brain is detected in wildlife (Basu et al 2007; Gebbink et al 2008; Montie et al 2009) and toxicokinetics studies, often by using radiolabeled PBDEs (Örn and Klasson-Wehler 1998; Riu et al 2008; Staskal et al 2006a, 2006b). In contrast, recent experimental and wildlife studies have shown that OH-PBDEs are usually not detectable in brain, although OH-PBDEs were detected in brain and cerebrospinal fluids of marine mammals (Gebbink et al 2008; Montie et al 2009; Zhang et al 2008).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Although BDE-47, the major congener found in people, is very persistent in the rat, it is rapidly eliminated unchanged in the urine of mice (Orn and Klasson-Wehler 1998). Recent studies from Staskal et al (2005) have suggested that BDE-47 may be a substrate for an active transport system in the kidney and/or may be highly bound to urinary proteins.…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…Orn and Klasson-Wehler (1998) studied the fate of BDE-47 in both mice and rats after a single oral dose. Although its behavior was as expected in rats (well absorbed, distribution to adipose and liver, long half-life, elimination in feces, limited metabolism), the parent compound was rapidly eliminated in the urine of mice.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Experimentally it has been shown that PBDEs are transformed into hydroxylated metabolites (OH-PBDEs) (Hakk and Letcher 2003) via routes similar to those for PCB congeners (Letcher et al 2000). The metabolism of BDE-47 in mice and rats (Örn and Klasson Wehler 1998) generates tri- and tetrabrominated hydroxylated metabolites, of which six OH-tetraBDEs and three OH-triBDEs have been identified structurally in rats (Marsh et al 2006). BDE-99 has been found to be metabolized to two pentabrominated and two tetra-brominated hydroxylated diphenyl ethers in the rat (Hakk et al 2002), and BDE-100 has generated five OH-pentaBDEs and six OH-tetraBDEs in the rat (Hakk et al 2006).…”
mentioning
confidence: 99%